The condition of the runway at Novolazarevskaya Station (East Antarctica) and the safety assessment of its use based on the 2021 research data - S. V. Popov; M. P. Kashkevich; A. S. Boronina (Лëд и снег, 2023)
Airbase Novo Runway has the status of the largest transport hub in the northern part of Antarctica, which can land large airlifter on wheeled chassis. However, the unsteady flow of the glacier leads both to the formation of hazardous glacial crevasses and changes the configuration of the runway. The purpose of this study was to investigation the state of the Novo Runway and to identify the degree of uneven flow of the glacier in this area. The article shows the results of research carried out from late October to mid-December 2021. Field work included GPR profiling, tacheometric survey, mechanical drilling, and downhole thermometry. The tacheometric survey was carried out at the beginning and at the end of the field work (in 42 days) to determine the displacements of pickets fixed on the glacier and then to calculate the glacier deformation rates. The results of the studies showed that there are no open crevasses in this area, which pose a danger to aircraft. There are non-hazardous healed crevasses at the beginning and end of the runway. At the same time, GPR data indicate that in the central part of the runway (at the distances from 1720 meters to 2240 meters from its beginning), there is a zone of junction of glacial flows. This zone is traced on parallel profiles for more than one kilometer. Calculation results indicate that the strain rates in this area in the transverse direction (across the runway) reaches -0.183 year-1. This corresponds to deformations (compressions) of more than 1.4 meters over 42 days of observations in absolute terms. Although these values significantly exceed the threshold values, there were no open crevasses in the glacier. It can be assumed that relatively recently the glacier flowed more slowly than now. This research should be continued to draw broader conclusions about the dynamics of the glacier in the area of the Novo Runway.